Information technology outsourcing relationship integration: a critical success factors study based on ranking problems (P.γ) and correlation analysis. Issue 1 (21st February 2017) - de Carvalho, Victor Diogho Heuer; Poleto, Thiago; Seixas, Ana Paula Cabral
Abstract: Information technology (IT) outsourcing is an interesting alternative for companies that want to obtain certain benefits by delegating IT activities to a provider to keep their focus on their core activities. This outsourcing involves a process that begins with the provider selection, passing through a series of negotiations, and reaching the definition of a contract, which will guide and delimitate the execution of activities, the interaction, and the relationship between the involved parties. To ensure the success of this relationship, several factors under contractual and relational governances have been defined in the literature. This work aims to corroborate the importance of literature findings about contractual aspects and critical success factors by presenting a ranking and correlation analysis and emphasize that companies may use these factors as criteria to improve their outsourcing relationships by developing a partnership status. To meet this objective, we established the main aspects and factors based on the literature, resulting in specific sets. Then, a survey was conducted with outsourcers and providers in the Recife's IT pole (Pernambuco, Brazil) to collect data and determine the relative importance and correlations between the elements of these sets using a methodology based on ranking problems (P.γ) and nonparametrical correlation analysis.